SISTEM PENILAIAN ESAI OTOMATIS PADA E-LEARNING DENGAN ALGORITMA WINNOWING - Astutik, Sariyanti; Cahyani, Andharini Dwi; Sophan, Mochammad Kautsar (Jurnal Informatika, 2014)
Exam essay is an evaluation of learning in the form of essay questions that have answers more variable than multiple choice questions. Variations of these answers provide its own difficulties for teachers in assessing response. Essay grading system is built to be one solution that can speed up and simplify the process of grading. Essay grading system in this study was done by measuring the similarity of responses of the students and teacher answer key. This research use winnowing algorithm. Winnowing algorithm is an algorithm for text similarity measure. Winnowing algorithm produces fingerprint of text that will represent the answer to the calculation of similarity with jaccard coeficient equation. Testing was conducted to determine the ability of the algorithm winnowing to provide an essay grading using n-gram and window value changes of the winnowing algorithm. The test results showed the use of the value of n-grams and window on the method of winnowing effect on fingerprint similarities were found. The more similarities fingerprint found, the value of the resulting system also be higher. The accuracy of the grading system showed better results on text answers that have the answer sentence structure same with key answer.